2023
DOI: 10.3390/agriculture13071349
|View full text |Cite
|
Sign up to set email alerts
|

IO-YOLOv5: Improved Pig Detection under Various Illuminations and Heavy Occlusion

Abstract: Accurate detection and counting of live pigs are integral to scientific breeding and production in intelligent agriculture. However, existing pig counting methods are challenged by heavy occlusion and varying illumination conditions. To overcome these challenges, we proposed IO-YOLOv5 (Illumination-Occlusion YOLOv5), an improved network that expands on the YOLOv5 framework with three key contributions. Firstly, we introduced the Simple Attention Receptive Field Block (SARFB) module to expand the receptive fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We also found some existing research used in the detection of pigs with YOLOv5 (e.g., Lai [38], Li [39], and Zhou [40]) and compared them with our method. The specific results are shown in Table 6 and were assessed using the mAP@0.5 metric: From Table 6, it can be seen that our YOLOv5-SA performs the best.…”
Section: Discussionmentioning
confidence: 99%
“…We also found some existing research used in the detection of pigs with YOLOv5 (e.g., Lai [38], Li [39], and Zhou [40]) and compared them with our method. The specific results are shown in Table 6 and were assessed using the mAP@0.5 metric: From Table 6, it can be seen that our YOLOv5-SA performs the best.…”
Section: Discussionmentioning
confidence: 99%
“…Attention for Accuracy (Not Report Speed/Model Size) [13] Attention for Accuracy (Not Report Speed/Model Size) [25] Attention for Accuracy (Speed Degradation) [26] Attention for Accuracy (Model Size Increase) [39] Pruning for Speed (Not Report Accuracy) [18] Spatial Attention-based Pruning for Accuracy and Speed Proposed Method…”
Section: Image Classificationmentioning
confidence: 99%
“…In general, there exists an accuracy/speed trade-off, and therefore, introducing attention mechanisms to improve accuracy increases the resource requirements (time and memory), while pruning for speed sacrifices accuracy. For example, in [26], applying attention improved accuracy from 90.4% to 90.8%; however, the speed decreased slightly from 83FPS to 82FPS. Similarly, in [39], the application of attention improved accuracy from 95.2% to 97.2%; however, it was reported that the model size increased slightly from 13.7MB to 14.4MB.…”
Section: Introductionmentioning
confidence: 99%